2001
DOI: 10.1046/j.1365-2680.2001.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restraint stress on responsiveness of atria and vas deferens in Sprague–Dawley rats

Abstract: 1 The effects of stress in rats were evaluated by measuring changes in body weight and in responsiveness to noradrenaline (NA) in the isolated vas deferens and atria after the animals had been exposed to restraint or restraint and isolation. 2 Animals which were subjected to restraint alone (1 h day-1 for 3, 7 or 28 days) had a significantly reduced rate of body weight gain. This effect was not potentiated by the additional stress of isolation. 3 Restraint alone did not produce significant changes in the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similar desensitizing effects of stress on a 1 -receptors were reported in the peripheral nervous system, where chronic stress reduced the a 1 -stimulated contraction of the isolated vas deferens (Singh et al, 2001) and downregulated the density of a 1 -binding sites in the heart (Torda et al, 1985). Furthermore, endotoxin (lipopolysaccharide, LPS) and septic shock markedly desensitized and downregulated vascular a 1 -receptors (Suba et al, 1992;Wakabayashi et al, 1989).…”
Section: Effects Of Stress and Depression On Epi-a 1 -Systemmentioning
confidence: 55%
“…Similar desensitizing effects of stress on a 1 -receptors were reported in the peripheral nervous system, where chronic stress reduced the a 1 -stimulated contraction of the isolated vas deferens (Singh et al, 2001) and downregulated the density of a 1 -binding sites in the heart (Torda et al, 1985). Furthermore, endotoxin (lipopolysaccharide, LPS) and septic shock markedly desensitized and downregulated vascular a 1 -receptors (Suba et al, 1992;Wakabayashi et al, 1989).…”
Section: Effects Of Stress and Depression On Epi-a 1 -Systemmentioning
confidence: 55%
“…It has previously been shown that repeated stress causes the vas deferens to become hypersensitive to NAd (Singh et al 2001, Einstein et al 2004. In this study, it was found that the vas deferens from the restraint-associated mice had a significantly higher responsiveness to NAd than the vas deferens isolated from the handlingassociated mice.…”
Section: Discussionmentioning
confidence: 47%
“…Prolonged sympathetic activity due to chronic stress can cause lasting changes in the physiology of the animal. One change that has been observed following chronic stress is hypersensitivity of the vas deferens to NAd in both mice and rats (Singh et al 2001, Einstein et al 2004).…”
mentioning
confidence: 99%
“…As far as gastrointestinal function, experiments carried out on gastric myoelectric activity in rhesus monkeys during flight, showed contrasting alterations between the subjects studied (Badakva & Miller, 2000). The vas deferens seems to be an organ that is highly sensitive to extreme conditions, such as microgravity, that can involve also a stressful component, since the responsiveness of vas deferens to NA has been shown to be increased by stress (Singh, Einstein & Lavidis, 2001).…”
Section: Introductionmentioning
confidence: 99%